Distribution of the diffuse interstellar band λ6614 in the NGC 2264, Rosette Nebula, and S147 regions. Issue 3 (22nd February 2022) - Ma, Wen-Jing; Chen, Jian-Jun; Li, Yin-Bi; Wu, Ke-Fei; Zhang, Wei; Chen, Xiang-lei; Luo, A-Li; Ren, Juan-Juan; Wu, Chao-Jian; Wu, Hong
ABSTRACT: Diffuse interstellar bands (DIBs) are absorption features arising from the interstellar medium, for which the carriers remain unclear. In this work, a total of 3115 stars in the regions of NGC 2264, the Rosette Nebula, and S147 are selected from LAMOST-MRS to study the spatial and velocity distributions of the DIB λ6614 carrier. From the spatial distribution, we find that DIB λ6614 carrier clouds appear to be widely and inhomogeneously distributed in the three target regions. They are either closer or further in distance, or much wider than the three nebulae, and there are gaps within them. The radial velocities of the DIB λ6614 carrier clouds are on average about 13, 20, and 10 km s −1 slower than the radial velocities of the nebulae in the NGC 2264, Rosette Nebula, and S147 regions, respectively. Furthermore, there is probably a high-extinction region from 0.6 to 0.8 kpc in the NGC 2264 direction, where the DIB λ6614 carrier vanishes. In the S147 region, the DIB λ6614 cloud is possibly discontinuous, and the tomographic evidence suggests that there are two DIB λ6614 clouds. The first cloud is at 0.3–0.9 kpc, which is in or near the Local Arm, while the second one emerges at about 1.8 kpc from the Sun and may be associated with S147 and in the Perseus Arm.